Dlbs1033 reduces blood pressure of hypertensive wistar-strain rats - Suryono, Suryono (Folia Medica Indonesiana, 2016)
The purpose of this study was to determine the effects of DLBS1033 on blood pressure reduction in hypertension–induced wistar strain rats. Design used in this study was true experimental design. The study was conducted at Biomedical Laboratory, Physiology, Faculty of Dentistry, Jember University, and Clinical and Community Pharmacy Laboratory, Pharmacy Faculty, Jember University. Subjects were taken from male Wistar rats aged 2-3 months, weighing 150-200 grams, as many as 22 rats. Intervention samples were induced into hypertension by giving prednisone in a dose of 1.5 mg/kg/day orally and 2% NaCl followed DLBS1033 of 0.5 grams/kgbw/day orally in the treatment group. T test results on systolic blood pressure (p = 0.00), which was <0.05, showing significant differences in systolic blood pressure in treatment groups. It can be concluded that DLBS1033 can lower systolic blood pressure in wistar rats with induced hypertension using prednisone 1.5 mg/kgbw/day and NaCl 2%.